Myliobatis freminvillii, bullnose eagle ray - Carlson, J.; Charvet, P.; Avalos, C.; Blanco Parra, M. P.; Briones Bell lloch, A.; Cardeñosa, D.; Chiaramonte, Gustavo Enrique; Cuevas, J.M.; Derrick, D.; Espinoza, E.; Mejía Falla, P. A.; Morales Saldaña, J. M.; et al.
The Bullnose Eagle Ray (Myliobatis freminvillii) is a medium-sized (to 106 cm disc width) demersal coastal eagle ray that occurs in the Northwest, Western Central, and Southwest Atlantic Oceans from Massachussetts, USA to the Texas coast of the Gulf of Mexico and from Venezuela to Buenos Aires, Argentina and inhabits continental shelves from the surface to a depth of 122 m. Its is captured by artisanal longlines, gillnets, beach seines and also in industrial shrimp trawls. In the Northwest Atlantic, population trend data are available from a deep-water trawl survey in the northern Gulf of Mexico that reveal steep increases in abundance over 2002-2013. There are no known threats in the Northwest and Western Central Atlantic, but in the Southwest Atlantic artisanal fisheries are intense. Further, there are largely unmanaged commercial trawl and longline fisheries in this area. This inshore eagle ray is exposed to intense and often unmanaged fishing pressure throughout the Southwest Atlantic portion of its range, and it has no refuge at depth. Due to the level of exploitation by widespread artisanal fisheries which lack adequate management, it is suspected that this species has undergone a population reduction of >80% over the past three generation lengths (44 years) in the Atlantic South American part of its range, but is stable in the Northwest and Western Central Atlantic. Overall, based on its range, with almost all threats found in the Southwest Atlantic, and the suspected low productivity of the species, the Bullnose Eagle Ray is suspected to have undergone a population reduction of 30-49% in the past three generation lengths (44 years) due to levels of exploitation, and it is assessed as Vulnerable A2bd. Fil: Carlson, J. National Marine Fisheries Service; Estados Unidos Fil: Charvet, P. Universidade Federal do Paraná; Brasil Fil: Avalos, C. Fundacion Mundo Azul; Guatemala Fil: Blanco Parra, M. P. Universidad de Quintana Roo; México Fil: Briones Bell lloch, A. Direccion de Regulaciones Pesqueras ...